Isolated Tuberculosis of the Rib in a 12-year-old Adolescent Boy: A Case Report from Iraq - Wasnaa Hadi Abdullah; Rihab Faisal Alabedi (Mustansiriya Medical Journal)
One of the major global health issues that still exist is tuberculosis (TB); primary tubercular osteomyelitis of the rib is an extremely rare entity. We present a case of isolated TB of the anterior fourth rib as the initial presentation, without any lung lesions. A high index of suspicion is necessary for the diagnosis of tubercular rib osteomyelitis. Usually, there is no significant morbidity and full remission following surgical removal of the affected rib in conjunction with the proper antitubercular therapy.